Overheating effect and hole-phonon interaction in SiGe heterostructures - Berkutov, I.B.; Andrievskii, V.V.; Komnik, Yu.F.; Myronov, M.; Mironov, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The effect of the charge carriers overheating in a two-dimensional (2D) hole gas in a Si1-xGex quantum well, where x = 0.13; 0.36; 0.8, 0.95, has been realized. The Shubnikov-de Haas (SdH) oscillation amplitude was used as a "thermometer" to measure the temperature of overheated holes. The temperature dependence of the hole-phonon relaxation time was found using analysis of dependence of amplitude of SdH oscillations change on temperature and applied electrical field. Analysis of the temperature dependence of the hole-phonon relaxation time exhibits transition of 2D system from regime of "partial inelasticity" to conditions of small angle scattering.